Examining Fluvial Stratigraphic Architecture Using Ground‐Penetrating Radar at the Fanta Stream Fossil and Archaeological Site, Central Ethiopia. Issue 6 (3rd August 2016) - Lanzarone, Peter; Garrison, Ervan; Bobe, René; Getahun, Assiged
Abstract : The Fanta Stream site is an archaeological and paleontological locality in Addis Ababa, Ethiopia. The site contains a rich assemblage of fossil mammals and Acheulean artifacts of approximately 600 ka located in a rare high‐altitude context. A ground‐penetrating radar (GPR) survey was conducted in order to provide three‐dimensional imaging of the subsurface, which the authors use to interpret the geometry and distribution of fossil‐containing stratigraphic units. Utilizing the stream's natural cut bank exposure, we calibrate GPR data to known geologic units through radar facies analysis. Shallow, high‐amplitude coherent reflection geometries are attributed to volcanic tuff deposits, as these units exhibit subparallel continuous reflections consistent with planar stratified sedimentary deposition. Deeper, discontinuous reflection packages are interpreted as conglomeritic, fossil‐containing deposits. The results of the GPR survey outline the location of the Fanta Stream's paleodepositional features as well as suggest the extent of fossiliferous stratigraphic units for use in future excavations.